Functional lipidomics: Palmitic acid impairs hepatocellular carcinoma development by modulating membrane fluidity and glucose metabolism. Issue 2 (16th June 2017) - Lin, Ling; Ding, Ying; Wang, Yi; Wang, Zhenxin; Yin, Xuefei; Yan, Guoquan; Zhang, Lei; Yang, Pengyuan; Shen, Huali
Abstract : Lipids are essential cellular components and energy sources of living organisms, and altered lipid composition is increasingly recognized as a signature of cancer. We performed lipidomic analysis in a series of hepatocellular carcinoma (HCC) cells and identified over 1, 700 intact lipids originating from three major lipid categories. Comparative lipidomic screening revealed that 93 significantly changed lipids and decreased palmitic acyl (C16:0)–containing glycerophospholipids were positively associated with metastatic abilities of HCC cells. Furthermore, both in vitro and in vivo experiments demonstrated that C16:0 incubation specifically reduced malignant cell proliferation, impaired cell invasiveness, and suppressed tumor growth in mouse xenograft models. Biochemical experiments demonstrated that C16:0 treatment decreased cell membrane fluidity and limited glucose metabolism. A phosphoproteomics approach further revealed such C16:0 incubation attenuated phosphorylation levels of mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription 3 (STAT3) pathway proteins. Multiple reaction monitoring analysis of 443 lipid molecules showed 8 reduced C16:0‐containing lipids out of total 10 altered lipids when cancer tissues were compared with adjacent nontumor tissues in a cohort of clinical HCC specimens ( P < 0.05). Conclusion : These data collectively demonstrate the biomedical potential of using altered lipid metabolism as a diagnostic marker for cancerous cells and open an opportunity for treating aggressive HCCs by targeting altered C16:0 metabolism. (Hepatology 2017;66:432–448).